Intracardiac Thrombi in Preterm Infants—A Case Study and Review of the Literature - Ayala Gover; Dawod Sharif; Liat Yaniv; Arieh Riskin (Diagnostics, 2023)
Intracardiac thrombi in preterm infants are not common but may lead to fatal outcomes. Predisposing and risk factors include small vessel size, hemodynamic instability, immaturity of the fibrinolytic system, indwelling central catheters and sepsis. In this paper, we present our own experience with a case of a catheter-related right atrial thrombus in a preterm infant, which was successfully treated with an aspiration thrombectomy. Then, we review the literature on intracardiac thrombosis in preterm infants: epidemiology, pathophysiology, clinical signs, echocardiographic diagnostic features and treatment options are discussed.